2023
DOI: 10.1093/jambio/lxad170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clostridium butyricum on the formation of primary choledocholithiasis based on intestinal microbiome and metabolome analysis

Abstract: Aims To investigate the function and probable mechanism of Clostridium butyricum in the development of choledocholithiasis. Methods and results The lithogenic diet group and the lithogenic diet + C. butyricum group were used to develop the choledocholithiasis model. During the experiment, Clostridium butyricum suspension was administered to the rats in the lithogenic diet + C. butyricum group. The findings demonstrated that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In our research, the Genus Clostridiumsensustricto1 displayed a positive association with the risk of GSD. Several earlier investigations have documented an association between Clostridium and GSD ( Grigor'eva and Romanova, 2020 ; Li et al, 2023 ). These findings indicate that Clostridiumsensustricto1 could potentially be considered a contributing factor to GSD.…”
Section: Discussionmentioning
confidence: 98%
“…In our research, the Genus Clostridiumsensustricto1 displayed a positive association with the risk of GSD. Several earlier investigations have documented an association between Clostridium and GSD ( Grigor'eva and Romanova, 2020 ; Li et al, 2023 ). These findings indicate that Clostridiumsensustricto1 could potentially be considered a contributing factor to GSD.…”
Section: Discussionmentioning
confidence: 98%
“…Compared to the normal control group, the abundance of the phylum Firmicutes, the proportion of Firmicutes/Bacteroidetes, and the genus Desulfovibrio were significantly increased in a lithogenic mouse model. The relative abundance of Bacteroidetes and Prevotella was decreased (Li et al, 2023). Hu et al found that Desulfovibrionales was enriched in patients with GS.…”
Section: Gallstones and Intestinal Bacteriamentioning
confidence: 99%